The Influence of Learning Media Use Audio visual on Student Learning Outcomes On the Subject of Moral Beliefs at MAN 2 Bandung Regency - Muhammad Rizky Ali Maulana; Supala; Huda, Miftahul; Imas Kurniasih; Mukhlishah; Salam, Moch Fadlani (Zona Education Indonesia, 2025)
Audio-visual learning media are channels of message delivery that utilize the senses of hearing and sight. In the subject of Akidah Akhlak, they serve as a bridge to enhance student learning outcomes. Learning outcomes are the results achieved in the form of numbers or scores obtained after being given a learning outcome test at the end of each lesson. The use of audio-visual learning media in the subject of Akidah Akhlak can be a bridge to improve student learning outcomes. The purpose of this study is to determine 1) the percentage level of the use of audio-visual learning media, 2) the percentage of student learning outcomes in the subject of Akidah, 3) the extent of the influence of using audio-visual learning media on student learning outcomes. This research uses a quantitative approach with a total of 36 respondents, and data collection tools in the form of observation, questionnaires, and documentation. The results showed that: 1) The use of audio-visual learning media in the subject of Akidah Akhlak obtained a percentage score of 38% in the sufficient category; 2) Student learning outcomes in the subject of Akidah Akhlak obtained a percentage score of 44.4% in the sufficient category; 3) The influence of using audio-visual learning media on student learning outcomes in the subject of Akidah Akhlak had a very significant effect with a percentage score of 94%.